Can public officials correctly be said to have obligations to future generations? - Frederickson H. George
Can public officials correctly be said to have obligations to future generations? Issue of international fairness are all around us. Begining with the American Oath, the author reviews moral, philosophical, and empirical arguments about the obligations of public officials toward future generations. A review of philosophers, both ancient and contemporary, finds general agreeement that temporal generations have moral responsibilities towards both their children (near term future generations through time). Using the compound theory of social equity, the author finds many examle of intergene rational equity in making and implementing of public policy. Findily, he calls for a moral community in public administrati
Keywords: Public Officers -- U.S.A.; Officials and Employees -- U.S.A.